Impact of marine protected areas on economical important coral reef fish communities: An evaluation of the biological monitoring of coral reef fish in Anambas Islands, Indonesia - RISANDI DWIRAMA PUTRA; RIKOH MANOGAR SIRINGIRINGO; Ani Suryanti; NI WAYAN PURNAMA SARI; MUIN SINAGA; NUNING VITA HIDAYATI; FRENSLY DAMIANUS HUKOM; MUHAMMAD ABRAR; PETRUS CHRISTIANUS MAKATIPU; RIDHO SIANTURI; YUWANDA ILHAM (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Putra RD, Siringiringo RM, Suryanti A, Sari NWP, Sinaga M, Hidayati NV, Hukom FD, Abrar M, Makatipu PC, Sianturi R, Ilham Y. 2021. Impact of marine protected areas on economical important coral reef fish communities: An evaluation of the biological monitoring of coral reef fish in Anambas Islands, Indonesia. Biodiversitas 22: 4169-4181. The use of Marine Protected Areas (MPAs) is the core strategy to reduce the impact of the anthropogenic stressor on marine fisheries, especially in reducing the overexploitation of fisheries resources and destructive fishing in which this plays a significant role in the conservation of marine biodiversity and populations. We conducted a study over 4 years to evaluate and assess the impact of MPAs on economically important reef fish in the Anambas Islands. We compared density, size, biomass, and diversity indices from the seven families of coral reef fish (Acanthuridae, Haemulidae, Lethrinidae, Lutjanidae, Scaridae, Siganidae, and Serranidae) using Underwater Visual Census (UVC) with a total of 12 MPAs stations (70-m transect). Multivariate analysis of variance (MANOVA) was used to evaluate and assess reserve protection on the coral reef fish, and several ecological indices were used to compare the potential change of economically coral reef fish diversity. We also measured the rate of change in coral cover to identify the effectiveness of the MPAs. After 4 years of studies, our result showed that there was an increase of economical reefs. Fish diversity, density, and biomass increased by 244%, 257%, and 179% respectively. There was no significant difference in the rate of coral cover change among MPAs stations. Economical coral reef fish in Anambas Islands were restored in marine reserve overtimes after fisheries restriction protection, but this does not change the rate of coral cover through time. In addition, the government managed and increased community awareness that significantly influenced decreasing destructive fishing practices and overexploited reef fish species in Anambas Islands but no change in coral cover. The MPAs environmental condition and natural disturbance, including thermal stress and high sedimentation, play a key role in coral cover recovery besides fisheries restriction in the MPAs area.